LONGPOP and IDS. Personal reflections on our collaboration With Kees Mandemakers. - Jenkinson, Sam; Matsuo, Hideko; Matthijs, Koen (Historical Life Course Studies, 2021)
The Leuven research team working on historical demography is grateful for their opportunity to have collaboratively and intensively worked with Professor Dr. Kees Mandemakers over an extended period of time. We wish him a wonderful emeritus status, not only in academia, but also in the warm nest of his family, relatives, children, and grandchildren. The three of us have known Kees for some time, but most closely since 2014, when we became formally engaged as project partners under the so-called LONGPOP-project, an EU funded Marie Curie grant, named Methodologies and Data mining techniques for the analysis of Big Data based on Longitudinal Population and Epidemiological Registers. The importance of our close professional relationship is best demonstrated by our work in producing the COR*-IDS 2020 database. The historical demographic dataset for the Antwerp arrondissement, a letter sample COR*-2010, recorded total sample size of +/- 33,000 residents of Antwerp for nearly seven decades and was already available. The LONGPOP project began in Autumn 2016, setting in motion a collaboration between ourselves at KU Leuven and Kees and his colleagues at the IISH. From the outset, we had purposefully worked closely with Kees’ team, utilising their premier expertise in database management and the IDS towards the new release of our database, the Antwerp COR*-IDS dataset. Here we set out our recollections of that intellectual process, encompassing the personal and professional reflections of our close working relationship.